Activation of GABA(A) receptors inhibits T cell proliferation. - Emma L Sparrow; Sonya James; Khiyam Hussain; Stephen A Beers; Mark S Cragg; Yury D Bogdanov (PLoS ONE)
Background The major sites for fast synaptic inhibition in the central nervous system (CNS) are ion channels activated by γ-aminobutyric acid (GABA). These receptors are referred as GABA(A) receptors (GABA(A)R). Recent evidence indicates a role of GABA(A)R in modulating the immune response. This work aimed to discern the role of GABA and GABA(A)Rs in human and mouse T cell activity. Methods Mouse splenocytes or human peripheral blood mononuclear cells (PBMCs) were activated with anti-CD3 antibodies and the proliferation of both CD8+ and CD4+ T cells assessed through flow cytometry. Subsequently, the effects on T cell proliferation of either GABA(A)R modulation by diazepam that is also capable of activating mitochondrial based translocator protein (TSPO), alprazolam and allopregnanolone or inhibition by bicucculine methiodide (BMI) and (1,2,5,6-Tetrahydropyridin-4-yl)methylphosphinic acid (TPMPA) were assessed. Results Positive modulation of GABA(A)Rs either by benzodiazepines or the neurosteroid allopregnanolone inhibits both mouse and human T cell proliferation. GABAergic inhibition of T cell proliferation by benzodiazepines could be rescued by GABA(A)R blocking. Our data suggest that benzodiazepines influence T cell proliferation through both TSPO and GABA(A)Rs activation. Conclusions We conclude that activation of GABA(A)Rs provides immunosuppression by inhibiting T cell proliferation.